PENATALAKSANAAN TERAPI MUROTAL UNTUK PENCEGAHAN STRES DAN MENGURANGI INSOMNIA PADA JAMAAH MUSLIMAH - Mardliyah; Yulia Ardiyanti; Siti Munawaroh; Alvi Ratna Yuliana (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Stress and sleep disturbances, particularly insomnia, are common problems experienced by adult women and can negatively affect physical and psychological well-being. One non-pharmacological intervention that is easy to apply and culturally acceptable among Muslim communities is murotal therapy. This community service activity aimed to provide education and implement murotal therapy as an effort to prevent stress and reduce insomnia among Muslim women at Masjid Rabiatul Adawiyah Kalisoka Tegal. The activity was conducted on October 20, 2024, involving approximately 78 Muslim women participants. The methods used included health education, demonstration, and guided practice of murotal therapy. The results showed that participants were able to understand the benefits of murotal therapy and demonstrated enthusiasm in practicing the therapy independently. Participants also reported feeling more relaxed and experiencing improved sleep quality after the intervention. This community service activity concluded that murotal therapy can be applied as a complementary intervention to help prevent stress and reduce insomnia among Muslim women.